2018
DOI: 10.1007/s00404-018-4821-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron supplementation during early pregnancy on the development of gestational hypertension and pre-eclampsia

Abstract: In our study population, iron supplementation before 16 weeks' GA was significantly associated with increased risk of developing de novo hypertension after 20 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…It was found that a high level of hemoglobin in women supplemented with iron was associated with an increase in the frequency of adverse effects, including preeclampsia [8,27]. In the study by Jirakittidul et al [45] iron supplementation before 16 pregnancy week was associated with a significant increase in the risk of hypertension de novo after the 20th week of pregnancy. Ziaei et al [46] found that the administration of iron at the beginning of the second trimester of pregnancy in women with a hemoglobin concentration of >13.2 g/dL increased the risk of pregnancy-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a high level of hemoglobin in women supplemented with iron was associated with an increase in the frequency of adverse effects, including preeclampsia [8,27]. In the study by Jirakittidul et al [45] iron supplementation before 16 pregnancy week was associated with a significant increase in the risk of hypertension de novo after the 20th week of pregnancy. Ziaei et al [46] found that the administration of iron at the beginning of the second trimester of pregnancy in women with a hemoglobin concentration of >13.2 g/dL increased the risk of pregnancy-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Iron takes part in the formation of reactive forms of oxygen and is responsible for development of insulin resistance and reduced insulin secretion by the pancreatic beta cells [11,12]. Current research indicates a possible link between iron excess and risk of preeclampsia, especially among women supplementing iron before 16 weeks of gestation with normal Hgb concentration (Hgb > 13.2 g/dL at the beginning of the second trimester) [13][14][15].…”
Section: Ironmentioning
confidence: 99%
“…Inordinate supplementation, resulting from the simultaneous use of several multivitamin preparations, may also have a negative impact on the developing pregnancy, e.g., an increased risk of congenital defects in case of the excessive use of vitamin A [21]. Furthermore, it has recently been reported by numerous authors that unnecessary iron supplementation may contribute to negative pregnancy outcomes by increasing the risk of pregnancy-induced hypertension, pre-eclampsia or gestational diabetes mellitus [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%